On the helices in the Galilean space G3 - Ogrenmis, A. O.; Ergut, M.; Bektas, M. (Shiraz Univ, 2007)
T. Ikawa obtained an ordinary differential equation for the circular helix. Recently, the helix have been investigated by many differential geometers such as T., Ikawa, H. Balgetir, M. Bektas, M. Ergut, N. Ekmekci and H. H. Hacisalihoglu. In this paper, making use of this author's methods, we obtained characterizations of helix for a curve with respect to the Frenet frame in 3-dimensional Galilean space G(3).
Keywords: Galilean space; helix